2010
DOI: 10.1177/1063426610392039
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Involvement and the School Adjustment of Rural Students With and Without Disabilities

Abstract: Bullying involvement status (i.e., bully, victim, bully–victim) and school adjustment were examined in a sample of 1,389 fifth graders (745 female, 644 male) including 145 special education students who were served in general education classrooms for at least 50% of the day. The sample was drawn from 35 rural schools in seven states across all geographic areas of the United States. School adjustment difficulties including internalizing and externalizing behavior problems were most pronounced in students who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 87 publications
5
61
2
1
Order By: Relevance
“…Prevalence rates for each construct, based on high endorsement, ranged from 2.3% (bullying) to 8.8% (relational victimization), including bully–victims (2.8%), and were higher for students with disabilities compared with students without disabilities. These findings are consistent with dichotomized research using self‐report or secondhand reporting measures that suggests that students with disabilities are overrepresented as experiencing victimization (Farmer et al., ; Rose et al., ; Saylor & Leach, 2008), engaging in bullying behaviors (Rose et al., ), and representing a subgroup of students identified as bully–victims (Farmer et al., ).…”
Section: Discussionsupporting
confidence: 78%
“…Prevalence rates for each construct, based on high endorsement, ranged from 2.3% (bullying) to 8.8% (relational victimization), including bully–victims (2.8%), and were higher for students with disabilities compared with students without disabilities. These findings are consistent with dichotomized research using self‐report or secondhand reporting measures that suggests that students with disabilities are overrepresented as experiencing victimization (Farmer et al., ; Rose et al., ; Saylor & Leach, 2008), engaging in bullying behaviors (Rose et al., ), and representing a subgroup of students identified as bully–victims (Farmer et al., ).…”
Section: Discussionsupporting
confidence: 78%
“…The risk for bullying and victimization is not equal across student groups; a number of studies indicate that students with disabilities or suffering from obesity, or the ones belonging to ethnic or sexual minorities, are at greater risk for being victimised than their peers. Farmer et al (2012) found that female students who received special education services were 3.9 times more likely to be victims and 4.8 times more likely to be bully-victims than their peers without disabilities. Similar results were also found in USA by Blake, Lund, Zhou, and Benz (2012).…”
Section: Prejudice-related Bullyingmentioning
confidence: 97%
“…The youth also experience increased social isolation or affiliate with peers who do not support or protect them from bullying (Rose et al 2013;Son et al 2014;Turner et al 2011). Youth with disabilities who are pure bullies tend to have higher levels of positive social characteristics and school bonding, and lower levels of school adjustment problems (Farmer et al 2012). Furthermore, students with disabilities who affiliate with aggressive peers and peers who were perceived to be popular by classmates tend to be more likely identified as bullies and were less likely to be victimized as compared with other students with disabilities (Estell et al 2009).…”
Section: Bullyingmentioning
confidence: 99%